Youth Court Research Project: a scoping study adopting a ‘whole-systems’ approach to the processing of cases in the Youth Courts - Kemp, Vicky (Legal Services Research Centre, 2008)
This study examined the processing of youth court cases prior to changes brought about by the Crime and Disorder Act 1998. The study adopted a ‘whole-systems’ review of the operation and efficiency of youth court cases in one county area. The key findings impacting on inefficiencies and delays identified included an adjournment culture in court, minor cases being brought inappropriately into court, the late production of evidence by the CPS and delays in negotiating with the defence (which led to cases proceeding unnecessarily to trial) and the management of cases by the defence and at court.